School Innovation and Prevention of Female Genital Mutilation, Genital Cutting (Revista Lusófona de Educação, 2024)
a Intervenção) Contra a Violência de Género, Tolerância Zero à Mutilação Genital Feminina/Corte dos Genitais(MGF/C), carried out in a Portuguese public education establishment. This is a school response, built in partnership with a Non-governmental Organization (NGO), mandated by the State Secretariat for Equality (SEI), with the aim of promoting the prevention of MGF/C in school audiences whose socio-cultural origin puts women and girls at imminent risk of being or becoming subject to this ancient practice. In the work, developed in the form of a Case Study, the project is examined with a view to examining its innovative educational potential, based on references proposed by various authors specializing in the subject and their contribution to the prevention of MGF/C based on educational dynamics carried out in a school environment.Keywords: innovation in education; fgm/c prevention; gender violence; intercultural dialogue.Keywords: innovation in education; fgm/c prevention; gender violence; intercultural dialogue.